Magnolia and the Signs of the Times: A Theological Reflection - DeGiglio-Bellemare, Mario (The journal of religion and film, 2000)
This piece attempts to articulate a theological reading of the film Magnolia, directed by P.T. Anderson. The author endeavours to locate God within the matrix of human relationality in the film. The God depicted in Magnolia, argues the author, is the God of liberation, the God who took the Israelites out of Egyptian slavery. This God of Exodus gives signs of imminent freedom to people living within systems of captivity which crush dreams and deny the flourishing of hope. Magnolia depicts the lives of people tossed aside by the television industry in Los Angeles. God's signs, however, remind us that it is precisely those who are tossed aside, or marginalized, who will find a new voice and help heal the brokenness of the world. The crowd was amazed when they saw the mute speaking, the maimed whole, the lame walking, and the blind seeing. And they praised the God of Israel. (Matthew 15:31)